ALGUNS ASPECTOS RELEVANTES NA COOPERAÇÃO EUROPEIA NO DOMINIO DA INFORMAÇÃO - Pacheco, Maria Fernanda Duarte (Cadernos BAD, 1987)
ALGUNS ASPECTOS RELEVANTES NA COOPERAÇÃO EUROPEIA NO DOMINIO DA INFORMAÇÃO